1992
DOI: 10.5254/1.3538653
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Spin Motional Analysis of Accelerated Sulfur Vulcanized Cis-Polyisoprene

Abstract: Spin-spin relaxation (T2) measurements were used to analyze the motional behavior of accelerated-sulfur vulcanized cis-polyisoprene. Biexponential decay behavior was found in all samples studied. This was modeled to consist of T2s (short) and T2l (long) components, with the T2s due to crosslinked regions and T2l due to regions distant from nodal points. T2 behavior was shown to depend strongly on crosslink density, but not to vary with concentration of cyclic structures. A simplified model was used for calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…62 The chemical structure, molecular weight and conformation of the elastomers affect the efficiency of sulfur vulcanization and the physical properties. 67 Layer 68 used the unique approach of 'vulcanizate recurring' to probe the role of sulfur and accelerators in the curing and reversion process. The crosslink density and distribution affect the physical properties and the stability on ageing and are dependent on accelerator type, ratio of accelerator to sulfur, reaction temperature and time.…”
Section: Accelerated Sulfur Vulcanizationmentioning
confidence: 99%
“…62 The chemical structure, molecular weight and conformation of the elastomers affect the efficiency of sulfur vulcanization and the physical properties. 67 Layer 68 used the unique approach of 'vulcanizate recurring' to probe the role of sulfur and accelerators in the curing and reversion process. The crosslink density and distribution affect the physical properties and the stability on ageing and are dependent on accelerator type, ratio of accelerator to sulfur, reaction temperature and time.…”
Section: Accelerated Sulfur Vulcanizationmentioning
confidence: 99%
“…Solid-state 13 C NMR spectroscopy was used to follow the magnitude of the ␥-gauche effect, which depends on the probability of finding gauche conformations, 35 and to study the molecular dynamics, especially relaxation times 36,37 of homogeneous polymer blends or heterogeneous charged rubber samples. 38 In this study, a series of three PMMAs will be adsorbed from a chloroform solution on a ␥-alumina powder and the influence of the PMMA tacticity on the nature and the amount of interactions at the interface will be investigated by FTIR and NMR spectroscopies. It will be shown that the adsorption not only creates interactions with the surface but also modifies the conformation of the polymer, both phenomena depending on the PMMA tacticity.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the level of the chain scission in the peroxide-vulcanized natural rubber is negligible 31,32 and also there is no spectral evidence for the presence of the chain scission in the TBBS-accelerated sulfur vulcanization of natural rubber. 14,17 Thus, the effect of the change in the molecular weight on the observed trend for Ec is small.…”
Section: Ec ϭ Chem 2[s] Chemmentioning
confidence: 94%
“…22 The chemical network chain density, chem , is then determined by solving the equation for each C1 obtained from the equilibrium-swelling result, e . It has been proposed that the amount of the chain entanglement increases with the level of chemical crosslinking or cure [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] but the appropriate correlation for the natural rubber system has not been proposed. Thus, the calculation in this study was based on the assumption that the contribution of the physical entanglement is constant during the extent of the vulcanization.…”
Section: Calculation Of the Chemical Crosslink Densitymentioning
confidence: 99%